2018
DOI: 10.1055/s-0038-1668526
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Section in the Management of Ovarian and Uterine Tumors: The Past 5 Years in a Tertiary Centre

Abstract: The IFS analysis plays an important role in selected situations and is associated to a high sensitivity and specificity in cases of ovarian and endometrial tumors. Its high accuracy is almost universally associated with the possibility of obtaining an optimal surgical treatment at the time of the first surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
5
7
0
Order By: Relevance
“…The mean age of the women for whom frozen section analysis was sent in this study was 49.2 years. This was similar to the observations noted in the study done by Aidos et al, in which the mean age noted was 51 years [ 4 ]. However, in the study done by Stephan et al, the mean age of women included in the study was 60.1 years [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age of the women for whom frozen section analysis was sent in this study was 49.2 years. This was similar to the observations noted in the study done by Aidos et al, in which the mean age noted was 51 years [ 4 ]. However, in the study done by Stephan et al, the mean age of women included in the study was 60.1 years [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, in the study done by Stephan et al, the mean age of women included in the study was 60.1 years [ 1 ]. According to this study, the frozen section's sensitivity is 94.11%, which was almost similar to the study done by Aidos et al, where the sensitivity was 96.9% [ 4 ]. However, the sensitivity of the frozen section in the studies done by Wang et al and Stephan et al was 84.2% and 90%, respectively [ 2 , 1 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the frozen section analysis has a variable role to play in different scenarios. In the case of ovarian and endometrial tumors, it has a high sensitivity and specificity [ 22 ]: whereas, in the case of excluding uterine sarcoma it isn't reliable. This is because for uterine sarcomas, multiple areas need to be sampled in order to establish a diagnosis wherein a frozen section is restricted to a limited tissue sample, making the chances of obtaining a false-negative result highly likely [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aidos et al . performed a study on 286 patients and demonstrated that the sensitivity of the frozen section examination was 96.25% in diagnosing endometrial cancer and in determining the depth of myometrial invasion ( 12 ). A meta-analysis reports that the frozen section examination was the gold standard in endometrial cancer, especially in determining the depth of myometrial invasion ( 13 ).…”
Section: Discussionmentioning
confidence: 99%